Host, Agent, and Environmental Determinants of Postoperative Nausea and Vomiting Following Spinal Anesthesia: A Systematic Review Using the Epidemiological Triad Framework - Mutia Putri Anggraini; Humaryanto Humaryanto; Ummi Kalsum (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Postoperative nausea and vomiting (PONV) remains one of the most common complications following spinal anesthesia and may adversely affect patient recovery, satisfaction, and healthcare outcomes. Objective: This study aimed to identify and synthesize host, agent, and environmental determinants associated with PONV following spinal anesthesia using the Epidemiological Triad Framework. Method: A systematic review was conducted according to the PRISMA 2020 guidelines. Literature searches were performed in PubMed, Scopus, ScienceDirect, and Google Scholar for studies published between 2023 and 2025. Eligible studies included randomized controlled trials, cohort studies, observational studies, and quasi-experimental studies involving patients undergoing spinal anesthesia. Data were extracted, critically appraised using Joanna Briggs Institute tools, and synthesized narratively. Results and Discussion: Twelve studies met the inclusion criteria. The most frequently reported host determinants were previous history of PONV, motion sickness, female sex, younger age, and elevated body mass index. Agent-related determinants included opioid exposure, intrathecal morphine, and intrathecal fentanyl, whereas dexamethasone, propofol, clonidine, and opioid-sparing analgesic techniques demonstrated protective effects. Environmental determinants included cesarean section, prolonged fasting, inadequate perioperative hydration, and intraoperative nausea and vomiting. Conclusion: PONV following spinal anesthesia is a multifactorial condition resulting from interactions among host, agent, and environmental factors. Early risk assessment and comprehensive preventive strategies are essential to reduce PONV incidence and improve postoperative outcomes